2009
DOI: 10.1007/s10787-009-0020-1
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical observations relating to oxidant stress injury in Chernobyl clean-up workers (“liquidators”) from Latvia

Abstract: The NPP patients may be undergoing progressive reduction in blood oxidants accompanied by adaptation to oxidant stress injury due to the increased anti-oxidant activity measured in their plasma and blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Some authors, however, have found in humans that the levels of some antioxidants can even increase at low doses of radiation, although high levels of radiation may deplete antioxidants (Ivanenko & Burlakova ), and a recovery of oxidative status can be produced over time (Skesters et al . ). Indeed, the high degree of radioactive contamination found in the region of Chernobyl and the relative long time (28 years) elapsed since the accident make this an excellent scenario for investigating possible mechanisms of adaptation to ionizing radiation in natural populations.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some authors, however, have found in humans that the levels of some antioxidants can even increase at low doses of radiation, although high levels of radiation may deplete antioxidants (Ivanenko & Burlakova ), and a recovery of oxidative status can be produced over time (Skesters et al . ). Indeed, the high degree of radioactive contamination found in the region of Chernobyl and the relative long time (28 years) elapsed since the accident make this an excellent scenario for investigating possible mechanisms of adaptation to ionizing radiation in natural populations.…”
Section: Introductionmentioning
confidence: 97%
“…This is potentially plausible given the observed positive effect of low‐dose radiation on some antioxidants (Ivanenko & Burlakova ), the recovery in the antioxidant status a long time after exposure (Skesters et al . ), and the fact that many organisms in the Chernobyl region have been chronically exposed to low doses of radiation, conditions that may favour radio‐adaption (Tapio & Jacob ). Searching for adaptive responses to radiation in natural populations is of key importance as it can potentially determine the capacity of species to evolve physiological adaptations and thus differential susceptibilities to overcome environmental challenges such as those that occurred in Chernobyl and Fukushima (Somero ).…”
Section: Introductionmentioning
confidence: 99%